Revitalisasi Seni Paduan Suara di Komunitas Gereja Lokal: Studi Kasus di GPDI El Roi Sawahan Karanganyar - Yunani, Theo Ferdinand; Raharjo, Eko (Riwayat: Educational Journal of History and Humanities, 2025)
This article explores the revitalization of choir singing amidst the dominance of band-based music in local church worship practices, with a case study at the Pentecostal Church in Indonesia (GPdI) El Roi in Sawahan Village, Karanganyar. The study employed a qualitative case study approach to examine the strategies, music education values, and participation dynamics within the church choir. Data were collected through in-depth interviews, participatory observation, and church documentation. The findings reveal that the choir remains active through structured coaching, youth involvement in regeneration, and strong collective spirit. Beyond functioning as a worship ensemble, the choir serves as a non-formal music education medium that reinforces spiritual, social, and aesthetic values. These findings reinforce the discourse that community-based arts practices play a vital role in shaping religious identity and communal solidarity, even in non-urban settings. This research contributes to the development of arts education within religious community contexts.